GAYA BELAJAR DAN KOMPETENSI PEDAGOGIK GURU DAN DAMPAKNYA TERHADAP HASIL BELAJAR SISWA - Susan Daniel (Jurnal Penelitian dan Pendidikan IPS, 2016)
This research was conducted with the following objectives: (1) is there any influence of learning styles on students’ result of study class X IPS SMA Negeri 4 Palangkaraya. (2) Is there any influence of Competence Pedagogical IPS Teacher on students’ result of study class X IPS SMA Negeri 4 Palangkaraya.3) Is there a simultaneous effect between students' learning styles and Pedagogic Competence IPS Teacher towards on students’ result of study class X IPS SMA Negeri 4 Palangkaraya. The population of this study were students of Class X IPS SMA Negeri 4 Palangkaraya which consisted 203 students. The sample was taken by purposive sampling from each class as much as 30% of the number of students which consists of 60 students.  The results showed that Competencies Pedagogical IPS teacher had no significant effect, which means that in this case variations in approach to teaching methods that teachers do not influence on students’ result of study class X IPS SMA N              egeri 4 Palangkaraya. (2) The style of learning is no significant effect on students’ result of study class X IPS SMA Negeri 4 Palangkaraya. (3) Teachers Pedagogic Competence IPS and learning styles do not have a positive effect and are not significant on students’ result of study. So that changes in the level Pedagogic Competence IPS Teacher and learning style will not change students’ result of the study.